Age Structure and Growth of the Japanese Spanish Mackerel (Scomberomorus niphonius) in Korean Waters - Han Ju Kim; Hae-young Choi; Seong Yong Moon; Hae Won Lee; Jeong-hoon Lee; Sang Chul Yoon (Fishes, 2026)
In this study, we estimated the age and growth of S. niphonius using otolith-based age determination. Five hundred and thirty individuals were sampled from commercial fisheries and the National Institute of Fisheries Science research vessels in Korean waters between January and December 2024 and from June to September 2025. Fork length ranged from 30.4 to 112.1 cm and body weight ranged from 218.2 to 9360 g. Sagittal otoliths were transversely sectioned and examined under a microscope. The age-reading precision between the two independent readers exhibited a high agreement (percentage agreement = 96.0%, average percentage error = 5.49%, coefficient of variation = 7.76%). The observed age ranges were 0–10.1 years for females and 0–8.1 years for males. Estimated parameters of the von Bertalanffy growth function were L∞=119.77 cm, K=0.41 year−1, and t0=−0.83 for females, and L∞=97.00 cm, K=0.59 year−1, and t0=−0.64 for males. Females exhibited larger asymptotic lengths but lower growth coefficients than those of males, and growth differed significantly between sexes. These results constitute the first study of age and growth based on otoliths in Korean waters and contribute to improving the biological understanding and management of this species.